2014
DOI: 10.1007/s11999-014-3574-1
|View full text |Cite
|
Sign up to set email alerts
|

Is Stability of the Proximal Tibiofibular Joint Important in the Multiligament-injured Knee?

Abstract: Level IV, therapeutic study. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 28 publications
4
37
0
1
Order By: Relevance
“…Correlation with Lysholm scores ranged from 0.65 to 0.93, suggesting measurement of similar constructs 18 19 28. Correlation with Tegner activity scores was 0.56 in one study, suggesting measurement of a separate activity-related construct 28.…”
Section: Resultsmentioning
confidence: 89%
“…Correlation with Lysholm scores ranged from 0.65 to 0.93, suggesting measurement of similar constructs 18 19 28. Correlation with Tegner activity scores was 0.56 in one study, suggesting measurement of a separate activity-related construct 28.…”
Section: Resultsmentioning
confidence: 89%
“…Besides proximal tibiofibular joint disruption, asymmetric hyperextension of the injured knee is often used as an indicator to use a "twotailed" technique. 18,19 Currently, clinical outcome studies are sparse and have not demonstrated a clear benefit over fibularbased reconstructions. This is likely the result of poorly defined indications with very low number patient cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…A universally accepted indication for a two-tailed technique would be proximal tibiofibular joint disruption in the setting of a PLC injury. 18 Asymmetric hyperextension of the injured knee is typically an indication of the need for a two-tailed reconstruction technique. 19…”
Section: History and Physical Examinationmentioning
confidence: 99%
“…The cyst was not present on the initial MRI.Direct blunt force trauma to the knee has long been known to result in severe injuries to the knee causing posterolateral corner, multi-ligamentous knee, and CFN injuries. They have also been associated with instability of the STFJ (Fallon et al, 1994;Kapur et al, 2009;Jabara et al, 2014). The resultant stretch tends to affect a long segment of the CFN.…”
mentioning
confidence: 99%